DISASTER RISK FINANCING OPTIONS FOR DEVELOPING COUNTRY: A CASE STUDY OF VIETNAM - Dinh Duc Truong (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Natural catastrophes such as floods, droughts, earthquakes, typhoons, and tsunamis are common in Vietnam. Floods and hurricanes, on the other hand, are the most lethal natural disasters. The Vietnamese Government is doing all possible to put disaster risk reduction (DRR) at its top priority list. The Government has developed a number of important legislative documents, regulations, and plans to assess its risk and response to disasters, and it has prioritized partnerships with neighboring nations. Natural disaster-related economic losses, on the other hand, continue to grow in Vietnam. Natural catastrophes pose a substantial financial risk and cause severe budget instability. Disaster Risk Finance is a growing area that deals with natural catastrophes' fiscal and economic repercussions (e.g., cyclones, droughts, earthquakes, floods). This article examines the existing position, difficulties, and solutions for Vietnam's financial system responding to natural catastrophes.